Productivity Model for Multi-Fractured Horizontal Wells with Complex Fracture Networks in Shale Oil Reservoirs Considering Fluid Desorption and Two-Phase Behavior - Xin Liu; Ping Guo; Junjie Ren; Zhouhua Wang; Hanmin Tu (Energies)
Shale oil reservoirs are characterized by extremely low porosity and permeability, necessitating the utilization of multi-fractured horizontal wells (MFHWs) for their development. Additionally, the complex phase behavior and desorption effect of two-phase fluids make the fluid flow characteristics of shale oil reservoirs exceptionally intricate. However, there are no productivity models for MFHWs in shale oil reservoirs that incorporate the complex hydraulically fractured networks, the oil–gas desorption effect, and the phase change of oil and gas. In this study, we propose a novel productivity model for MFHWs in shale oil reservoirs that incorporates these complex factors. The conformal transformation, fractal theory, and pressure superposition principle are used to establish and solve the proposed model. The proposed model has been validated by comparing its predicted results with the field data and numerical simulation results. A detailed analysis is conducted on the factors that influence the productivity of shale oil wells. It is found that the phase behavior results in a significant 33% reduction in well productivity, while the fluid desorption leads to a significant 75% increase in well productivity. In summary, the proposed model has demonstrated promising practical applicability in predicting the productivity of MFHWs in shale oil reservoirs.